Untreated Superior Vena Cava Aneurysm: Radiological Significance and Review of the Literature - Abhinav Patel; Ryan Cobb; Victor Rivera; Scott Simpson (Case Reports in Radiology)
Superior vena cava (SVC) aneurysms are a rare entity. The majority of the literature is in the form of case reports. SVC aneurysms are often an incidental finding with iatrogenic, congenital, or idiopathic etiologies. Treatment goals focus on preventing theoretical rupture or thrombus formation. Management options include observation, conservative medical management, surgical excision, and thrombin injection. We present a 73-year-old female with an incidental SVC aneurysm discovered on computed tomography (CT) of the thorax. The patient was observed without intervention for greater than 6 years. No complications were attributable to the SVC aneurysm during follow-up or over the course of the patient’s life.